Analisis Karakteristik Organoleptik Nastar Tepung Sagu-Stevia untuk Diversifikasi Produk Kue Kering dalam Pelayanan Kuliner di Sektor Hospitality - Aprilia Nurcahyaning Rahayu; Tiara Cahyani Putri (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Innovation in low-calorie culinary products holds great potential to enrich offerings for tourists in the hospitality and tourism sectors, addressing the growing demand for healthier food options. This study aims to determine the differences in organoleptic characteristics of nastar made with sago flour and stevia as a natural sweetener. The experimental method was applied using two formulation samples: X (80% sago flour, 20% wheat flour, 0.009% stevia extract) and Y (100% sago flour, 0.009% stevia extract). Organoleptic tests were conducted with 15 untrained panelists using a hedonic scale to evaluate color, aroma, taste, and texture attributes. Data were analyzed using the Shapiro-Wilk normality test and the Wilcoxon signed-rank test. The results showed no significant differences (p > 0.05) between the two samples across all attributes. The average organoleptic scores fell within the “liked” category, with the highest scores found in sample Y for color and aroma. The use of 100% sago flour and stevia still produced nastar that was well-liked by panelists, without compromising sensory quality. This innovation presents a promising alternative for healthier local-based cookies and can be developed as an attractive product in the healthy culinary tourism sector.